Pengaruh Kualitas Produk dan Pelayanan terhadap Kepuasan Konsumen FOGO Brazilian BBQ, PIK, Jakarta - Kusumaningrum, Dewi Ayu; Simanjuntak, Vera Clara; Tannaka, Jessica (Jurnal Disrupsi Bisnis, 2024)
Restaurant management competition must always make changes or innovations and provide the best service to consumers so that consumers feel satisfied. Various factors influence consumer satisfaction, namely product quality and service quality. In recent times, the trend of restaurants that carry the All You Can Eat (AYCE) concept has become increasingly popular with the public, for example FOGO restaurants. The purpose of this research is to determine the effect of product and service quality on consumer satisfaction of FOGO Brazilian BBQ Pantai Indah Kapuk. The research method used is quantitative descriptive. Quantitative methods aim to test hypotheses. The independent variables are product quality (X1) and service quality (X2). The dependent variable is consumer satisfaction (Y). Data analysis using validity testing, reliability testing, classical assumption testing, and hypothesis testing. The research results show that there is an influence of product (X1) on consumer satisfaction (Y) FOGO Brazilian BBQ PIK, North Jakarta. However, there is no influence of service quality (X2) on consumer satisfaction (Y) FOGO Brazilian BBQ PIK, North Jakarta. There is an influence of product (X1) and service quality (X2) simultaneously (together) on consumer satisfaction (Y) FOGO Brazilian BBQ PIK, North Jakarta amounting to 69.1%.